2018
DOI: 10.1039/c8tc03003k
|View full text |Cite
|
Sign up to set email alerts
|

Novel BaTiO3-based lead-free ceramic capacitors featuring high energy storage density, high power density, and excellent stability

Abstract: High energy storage density and high power density combined in novel BaTiO3-based lead-free ceramics for multilayer ceramic capacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
165
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(174 citation statements)
references
References 48 publications
8
165
1
Order By: Relevance
“…According to the W D ‐t curves measured under different electric fields in Figure c, it is clear that the x = 0.1 ceramic exhibits a fast discharging speed under 20 kV mm −1 with a short discharge time of t 0.9 ≈97 ns (Figure S3b, Supporting Information), which describes the discharge time corresponding to the 90% saturated W D value. The t 0.9 value achieved in the x = 0.1 ceramic is much smaller than that of most reported relaxor FEs, AFEs, and polymer nanocomposite capacitors (usually on the level of hundreds of nanoseconds), as can be clearly seen in Table S2, Supporting Information. This fast discharging speed should be ascribed to a nearly linear and hysteresis‐free polarization response mainly from the ionic displacement (see Figure e).…”
mentioning
confidence: 69%
“…According to the W D ‐t curves measured under different electric fields in Figure c, it is clear that the x = 0.1 ceramic exhibits a fast discharging speed under 20 kV mm −1 with a short discharge time of t 0.9 ≈97 ns (Figure S3b, Supporting Information), which describes the discharge time corresponding to the 90% saturated W D value. The t 0.9 value achieved in the x = 0.1 ceramic is much smaller than that of most reported relaxor FEs, AFEs, and polymer nanocomposite capacitors (usually on the level of hundreds of nanoseconds), as can be clearly seen in Table S2, Supporting Information. This fast discharging speed should be ascribed to a nearly linear and hysteresis‐free polarization response mainly from the ionic displacement (see Figure e).…”
mentioning
confidence: 69%
“…Bismuth‐containing relaxors are believed to be promising alternatives for lead‐based relaxors as both Bi 3+ and Pb 2+ possess lone pair electronic configuration 6 s 2 which can be strongly hybridized with O 2 p orbitals, accounting for the high polarization and dielectric constant . Energy densities between 1‐3 J/cm 3 in BaTiO 3 ‐Bi(MeʹMeʺ)O 3 (Meʹ = Mg 2+ , Zn 2+ ; Meʺ = Ti 4+ , Nb 5+ ) relaxor ceramics have been reported, demonstrating they are potential candidates for lead‐free energy storage applications . On the other hand, bismuth‐modified strontium titanate ((Sr 0.7 Bi 0.2 )TiO 3 , SBT for short) was reported to possess strong relaxor characteristic, the substitution of trivalent Bi ions to divalent Sr ions in SrTiO 3 results in relaxor behavior and high polarization .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Energy densities between 1-3 J/cm 3 in BaTiO 3 -Bi(MeʹMeʺ)O 3 (Meʹ = Mg 2+ , Zn 2+ ; Meʺ = Ti 4+ , Nb 5+ ) relaxor ceramics have been reported, demonstrating they are potential candidates for lead-free energy storage applications. [14][15][16][17][18][19] On the other hand, bismuth-modified strontium titanate ((Sr 0.7 Bi 0.2 )TiO 3 , SBT for short) was reported to possess strong relaxor characteristic, the substitution of trivalent Bi ions to divalent Sr ions in SrTiO 3 results in relaxor behavior and high polarization. 20 Moreover, SBT has been used as end member to form solid solution dielectrics for energy storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5d, the m value for 6BMZ ceramic is 17, leading to a high level of confidence. The calculated E b of 6BMZ is 460 kV/cm which is much higher than other lead-free energy storage ceramics [32][33][34][35][36], as shown in Table 2. The energy storage properties of BaTiO 3 -Bi(Me Me")O 3 ceramics have been widely studied, and the obtained energy densities have been found to be around 1-3 J/cm 3 in previous research as shown in Table 2.…”
Section: Energy Storage Properties Of 094sbt-006bmz Ceramicmentioning
confidence: 82%